QUANTITATION OF METFORMIN IN URINE BY RP-HPLC METHOD AND ITS APPLICATION IN PHARMACOKINETICS - Y., MARY REBECCA; V., SUDHA; A., VIJAYAKUMAR; A. K., HEMANTH KUMAR (International Journal of Pharmacy and Pharmaceutical Sciences, 2021)
Objective: To develop and validate an easy and sensitive HPLC method for quantitation of metformin in urine. Methods: The technique involved deproteinisation of urine sample with methanol and analysis of the supernatant the usage of Zorbax 300–SCX, 4.6 X 150 mm ID, 5 µm particle size and UV detection at a wavelength of 233 nm. Results: The assay was specific for metformin and linear from 1.25 to 50.0μg/ml. The relative standard deviation of intra-and inter-day assays was lesser than 7%. The recovery of metformin from urine ranged from 97-103%. Conclusion: An easy and sensitive HPLC approach for quantitation of metformin in urine had been developed. Due to its simplicity in sample preparation and instrumentation, this technique can be used for pharmacokinetic studies of metformin in urine samples.